Neurosensory Differentiation and Innervation Patterning in the Human Fetal Vestibular End Organs between the Gestational Weeks 8–12 - Johnson Chacko, Lejo; Pechriggl, Elisabeth J.; Fritsch, Helga; Rask-Andersen, Helge; Blumer, Michael J. F.; Schrott-Fischer, Anneliese; Glueckert, Rudolf (Frontiers in Neuroanatomy, 2016)
Balance orientation depends on the precise operation of the vestibular end organs and the vestibular ganglion neurons. Previous research on the assemblage of the neuronal network in the developing fetal vestibular organ has been limited to data from animal models. Insights into the molecular expression profiles and signaling moieties involved in embryological development of the human fetal inner ear have been limited. We present an investigation of the cells of the vestibular end organs with specific focus on the hair cell differentiation and innervation pattern using an uninterrupted series of unique specimens from gestational weeks 8–12. Nerve fibers positive for peripherin innervate the entire fetal crista and utricle. While in rodents only the peripheral regions of the cristae and the extra-striolar region of the statolithic organs are stained. At week 9, transcription factors PAX2 and PAX8 were observed in the hair cells whereas PAX6 was observed for the first time among the supporting cells of the cristae and the satellite glial cells of the vestibular ganglia. Glutamine synthetase, a regulator of the neurotransmitter glutamate, is strongly expressed among satellite glia cells, transitional zones of the utricle and supporting cells in the sensory epithelium. At gestational week 11, electron microscopic examination reveals bouton contacts at hair cells and first signs of the formation of a protocalyx at type I hair cells. Our study provides first-hand insight into the fetal development of the vestibular end organs as well as their pattern of innervation by means of immunohistochemical and EM techniques, with the aim of contributing toward our understanding of balance development.